Dominant Air Pollution Source Determination in the Vicinity of Coking Plant Based on Statistical Data Analysis - Jan Bitta; Irena Pavlikova; Ondrej Zavila; Pavel Platos; Jose Maria Caridad y Ocerin (Communications - Scientific letters of the University of Zilina, 2015)
The goal of the article is to present the statistical analysis based determination of the dominant air pollution sources in one of the Ostrava pollution monitoring stations. Statistical analyses were based on correlation analysis and quantile-based time pattern analysis. These analyses were able to prove that benzene and toluene pollution is dominantly caused by the same pollution sources. The time pattern analysis then proved the dominance of a nearby cokery. Time pattern analyses also proved traffic to be the dominant source of NO2 pollution and PM10 pollution to be the mix of traffic, heating and industrial sources.